Geographic Features of Zero-Emissions Urban Mobility: the Case of Electric Buses in Europe and Belarus - Bezruchonak, Andrei (European Spatial Research and Policy, 2019)
This article reviews the emerging phenomena of electric buses’ deployment in Europe and Belarus within the general framework of the concept of sustainable and electric urban mobility. The author offers a brief overview of electric bus technologies available on the market and a spatial analysis of fleet deployment in Europe. The analysis of the spatial structure of the distribution of e-buses in Europe indicated that, in terms of the number of vehicles in operation, the UK and the Netherlands are the regional leaders, while in terms of the number of cities testing e-buses – Germany, Sweden, and Poland are the leaders. The analysis showed that the main factors supporting the distribution of innovative technology and public support are legislative and regulative framework as well as clear strategic planning and cooperation between local administrations and transportation authorities. Other important aspects, such as network building features, and the location of the charging infrastructure were also discussed. The analysis of the case study of Minsk (the first city to introduce electric buses in Belarus) outlined the typical limiting factors for all types of markets: high battery costs and dependency on infrastructure; recommendations are given to emphasise bus fleet replacement (instead of trolleybus) and to develop a comprehensive sustainable urban mobility strategy.